Reviewing cognitive distortions in managerial decision making: Toward an integrative co-evolutionary framework. Issue 5 (11th June 2018) - Abatecola, Gianpaolo; Caputo, Andrea; Cristofaro, Matteo
Abstract : Purpose: Why and how do cognitive distortions in managerial decision making occur? All organizations are imperfect systems (Katz and Kahn, 1966 ), with wrong decisions often just round the corner. As a consequence, addressing these important questions continues to be particularly lively in the management development area, especially in terms of its intended contribution to the de-biasing activity. Thus, the purpose of this paper is to provide the current scientific dialogue on the topic with updated lenses, which can also be innovative from some aspects. Design/methodology/approach: The review framework is based on the recent, impactful article on biases in managerial decision making by Kahneman et al. (2011), and on Bazerman and Moore's (2013) perspective on emanating heuristics, considered as the causes of biases. Accordingly, the authors derive four intertwined thematic clusters of heuristics, through which the authors systematically group and critically analyze the management literature mostly published on the topic since 2011. Findings: From the analyzed clusters the authors propose an integrative framework of emanating heuristics, which focuses on the co-evolving relationships and potentially self-reinforcing processes in and between them. Originality/value: The value of the contribution is threefold: from a methodological perspective, to the authors' knowledge, the studies adopted as the basis of the analysis have not yet been simultaneously used as a comprehensive ground for updated reviews on this topic; from a conceptual perspective, the emerging integrative co-evolutionary framework can help explain the dangerous connections among cognitive traps and emanating heuristics; and from a practical perspective, the resulting framework can also be helpful for future de-biasing attempts in the business arena.